Social and Ecological Dominance Orientations, Climate Change Denial, and Pro-Environmental Behaviour - Gözde Kıral Uçar; Meryem Kaynak Malatyalı‬‬; Bağdat Deniz Kaynak (Global Environmental Psychology)
This study was aimed at investigating the associations between social dominance orientation (SDO), ecological dominance orientation (EDO), climate change denial and past pro-environmental behaviour. A total of 348 individuals, aged between 18 and 61 years (M = 22.27; SD = 4.80), participated in this study. The results showed that SDO predicted all forms of climate change denial and past pro-environmental behaviour, although EDO only predicted denial of guilt. Additionally, the rationalisation of own involvement dimension of climate change denial, but no other dimensions of it, predicted past pro-environmental behaviour. Moreover, gender was a predictor of five dimensions of climate change denial and past pro-environmental behaviour.